Boron‐Made N2: Realization of a B≡B Triple Bond in the B2Al3− Cluster. Issue 36 (29th May 2020) - Fedik, Nikita; Mu, Chaonan; Popov, Ivan A.; Wang, Wei; Wang, Jie; Wang, Haopeng; Bowen, Kit H.; Boldyrev, Alexander I.; Zhang, Xinxing
Abstract: Until now, all B≡B triple bonds have been achieved by adopting two ligands in the L→B≡B←L manner. Herein, we report an alternative route of designing the B≡B bonds based on the assumption that by acquiring two extra electrons, an element with the atomic number Z can have properties similar to those of the element with the atomic number Z+2 . Specifically, we show that due to the electron donation from Al to B, the negatively charged B≡B kernel in the B2 Al3 − cluster mimics a triple N≡N bond. Comprehensive computational searches reveal that the global minimum structure of B2 Al3 − exhibits a direct B–B distance of 1.553 Å, and its calculated electron vertical detachment energies are in excellent agreement with the corresponding values of the experimental photoelectron spectrum. Chemical bonding analysis revealed one σ and two π bonds between the two B atoms, thus confirming a classical textbook B≡B triple bond, similar to that of N2 . Abstract : Triple the fun ! Electron donation from Al to B leads to the formation of a B≡B triple bond in an experimentally observed B2 Al3 − cluster (see figure).